Employers’ solutions for skill problems: make-or-buy and engagement with higher education - Araújo, Emília; Suleman, F.; Videira, P. (ICERI, 2019)
Abstract Higher education (HE) is being pressured to provide graduates with skills that match economic and labour market skill needs and foster their employability. At the same time, employers are faced with a range of skill problems and often blame HE for the ill-preparation of graduates for the world of work. Our research examines the solutions adopted by a set of employers to solve their skill shortages and explores the link between make-or-buy and employers’ engagement with HE in Portugal. The data were gathered in face-to-face semi-structured interviews with human resource managers and owners of 13 firms from the northern region of Portugal. Our results show that in spite of being faced with several skill shortages and deficits,employers resort mostly to internal training and to more passive forms of engagement with HE. Our results suggest that there are still considerable institutional barriers to forging a closer relationship between firms and HE.